Utilizing Search Engine Optimization (SEO) through SEO-Friendly Websites as a Digital Transformation of Online Marketing Strategies for MSMEs - Abdul Fattah, Fuad; Rusmana, Dede; Hidayat, Rachmad; Khoiril Mala, Iva (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Backround: The digital era has had a disruptive impact on various sectors, including the industrial sector. The industrial sector must be able to adapt to market its products using digital media in order to capture a wider market. The purpose of this community service is to provide assistance to MSMEs and equip them with the knowledge to implement digital marketing. Method: A workshop on creating and maintaining SEO-based websites was used to provide assistance to MSMEs so that they could gain more comprehensive knowledge accompanied by practical experience. Result: The use of SEO-based websites has successfully increased the visibility of MSMEs and MSME products to national and international audiences. Before the website existed, MSMEs had no visibility at all, but after the website was created, they were able to reach 1,274 views with 4 product posts. Conclusion: Community service activities can improve the capabilities of MSMEs in transforming traditional marketing to more modern marketing by using digital media such as SEO-friendly websites, thereby improving the performance of MSMEs.